2016
DOI: 10.1016/j.bpsc.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Altered Development of Amygdala-Anterior Cingulate Cortex Connectivity in Anxious Youth and Young Adults

Abstract: Background Development of cortico-amygdala circuitry underlies the maturation of emotion processing and regulation, and age-related changes in amygdala connectivity with anterior cingulate cortex (ACC) have been shown to mediate normative developmental decreases in anxiety. It remains unclear whether developmental changes in this circuitry relate to pathological anxiety in youth. The current functional magnetic resonance imaging (fMRI) study addresses this question by examining amygdala functional connectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 45 publications
7
51
3
2
Order By: Relevance
“…These findings suggest that a lack of developmental decrease in neural connectivity between CM amygdala and rACC associated with increases in anxiety and depression traits. In support of these findings, task-based neuroimaging studies of emotional face processing show a shift from positive to negative connectivity in amygdala fronto-limbic circuits during typical development (109); young adults with anxiety fail to show this change, suggesting that an altered pattern of age-associated changes in amygdala connectivity is associated with increased anxiety(110). Intriguingly, higher amygdala-vmPFC connectivity has been associated with anxiety in typically developing 7–9 years olds (50); however, the effects were strongest in the BL amygdala, not the CM amygdala.…”
Section: Discussionmentioning
confidence: 85%
“…These findings suggest that a lack of developmental decrease in neural connectivity between CM amygdala and rACC associated with increases in anxiety and depression traits. In support of these findings, task-based neuroimaging studies of emotional face processing show a shift from positive to negative connectivity in amygdala fronto-limbic circuits during typical development (109); young adults with anxiety fail to show this change, suggesting that an altered pattern of age-associated changes in amygdala connectivity is associated with increased anxiety(110). Intriguingly, higher amygdala-vmPFC connectivity has been associated with anxiety in typically developing 7–9 years olds (50); however, the effects were strongest in the BL amygdala, not the CM amygdala.…”
Section: Discussionmentioning
confidence: 85%
“…Alternatively, there may be differences in the direction of ACC activation depending on age and development. For example, recent work suggests that anxiety is characterized by altered developmental patterns of amygdala connectivity with ACC from childhood into young adulthood (Kujawa, Wu, et al., ). In addition, a separate study shows that age moderates the link between anxiety and the error‐related negativity, an event‐related potential component that is generated in the ACC (Meyer, Weinberg, Klein, & Hajcak, ).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that amygdala-PFC functional connectivity is not a reliable marker of neural development. Unlike cortical thickness which has been studied widely across large representative samples (for review see Vijayakumar et al, 2016), research documenting amygdala-PFC connectivity as a marker of maturation is more modest Kujawa et al, 2016;Silvers, Insel, et al, 2016b;Wu et al, 2016), and to our knowledge, all of the studies that have demonstrated a developmental shift in this circuit have been crosssectional. As such, amygdala-mPFC connectivity may be an unreliable marker of neural maturation.…”
Section: Ela and Brain Developmentmentioning
confidence: 99%